Filling material as well as preparation method and application thereof
The filling materials made of specific raw materials are solved by solving the problems of high impact force of fitness equipment when falling and the material is prone to deformation and breakage, achieving high mechanical properties, drop resistance and impact resistance of fitness equipment, reducing production costs.
Patent Information
- Application Number
- CN202411678614.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
Existing fitness equipment such as barbells, dumbbells, and kettlebells have a high impact when falling, which can easily damage the ground. At the same time, the rubber-made equipment is prone to deform and break during use, and the metal inner core is costly, making it difficult for the filling material to take into account the integration, impact resistance and mechanical strength.
Filling materials made by combining specific raw materials, including reactive polyurethane hot melt glue, wood particles, perlite, rubber particles, resin particles and coal ash, use the good elasticity, microporous structure and adhesive properties of these raw materials to form mechanical occlusion and chemical bonding to enhance the strength and integration of the filler material.
The filling materials have good mechanical properties, drop resistance and impact resistance in fitness equipment, reducing the risk of deformation and fracture of the equipment during use, and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fitness equipment, and in particular to a filling material and a preparation method and application thereof. Background Art
[0002] Barbells, dumbbells, kettlebells, etc. are commonly used fitness equipment for strength training. Most of them are made of cast iron. Since cast iron is heavy and has poor cushioning properties, during training, the barbells, dumbbells, kettlebells and other fitness equipment make a loud noise when they fall, causing a great impact on the fitness equipment itself, and also easily causing damage to the ground.
[0003] In order to prevent barbells, dumbbells, kettlebells and other fitness equipment from damaging the floor when they fall, all-rubber fitness equipment made of rubber has become a better choice. However, due to the light specific gravity and insufficient mechanical properties of rubber, it is easy to deform and break during the use of the product.
[0004] Putting a rubber cover on the metal core can reduce the impact when the fitness equipment falls, but the integrity is not strong and the rubber cover is easy to move and fall off. In addition, the cost of the pure metal core is relatively high. Filling the metal core with other fillers can reduce the cost, but general fillers are difficult to take into account the integrity, impact resistance and mechanical strength, and cannot be used for a long time. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a filling material and a preparation method and application thereof. By matching specific raw materials, the filling material prepared takes into account integrity, impact resistance and mechanical strength at the same time, and can be used to make fitness equipment such as barbells, dumbbells, kettlebells, etc.
[0006] In a first aspect, the present application provides a filling material for fitness equipment, which is implemented by the following technical solutions:
[0007] A filling material for fitness equipment, comprising the following raw materials in parts by weight: 5-10 parts of reactive polyurethane hot melt adhesive, 8-15 parts of wood particles, 10-25 parts of perlite, 5-12 parts of rubber particles, 5-12 parts of resin particles, 5-15 parts of coal ash, and 1-3 parts of water;
[0008] The reactive polyurethane hot melt adhesive comprises the following raw materials in parts by weight: 10-20 parts of polyester polyol, 20-40 parts of epoxy-modified polyether polyol, 2-6 parts of fumed silica, 5-10 parts of calcium sulfate whiskers, 6-10 parts of acrylic resin powder, 30-50 parts of diphenylmethane diisocyanate, 5-10 parts of N-n-butyl-3-aminopropyltrimethoxysilane, 1-5 parts of molecular sieve, 0.5-1 parts of catalyst, and 0.5-2 parts of dodecyldimethyl tertiary amine;
[0009] The preparation method of the epoxy-modified polyether polyol comprises the following steps:
[0010] S1. Take isophorone diisocyanate, add dibutyltin dilaurate, heat to 30-40 ° C, gradually add polyethylene glycol monomethyl ether dropwise within 25-35min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, and distill under reduced pressure at a temperature of 90-105 ° C to obtain an intermediate product;
[0011] S2. Take bisphenol A epoxy resin and heat it to 85-95 ° C. Under a protective gas atmosphere, phenylphosphonic acid is gradually added dropwise within 18-25 min. After the addition is completed, react for 2-3 hours, add benzyl triethylamine chloride and the intermediate product, react until NCO% is less than 0.1%, and distill under reduced pressure at 90-105 ° C to obtain epoxy-modified polyether polyol;
[0012] The molar ratio of the polyethylene glycol monomethyl ether to the isophorone diisocyanate in step S1 is 1:(1-1.3);
[0013] The molar ratio of the bisphenol A epoxy resin to the phenylphosphonic acid in step S2 is (4-5):2;
[0014] A filling material for fitness equipment according to an embodiment of the present application has at least the following beneficial effects:
[0015] The filling material of the present application is composed of different raw materials. Wood particles, rubber particles, and resin particles have good elasticity. Perlite and coal ash also have a microporous structure. Reactive polyurethane hot melt adhesive is added for bonding. The reactive polyurethane hot melt adhesive can penetrate into the tiny pores of the raw material matrix and form mechanical bite and chemical bonding with the raw materials, thereby enhancing the bonding force between the raw materials and improving the strength of the filling material.
[0016] The perlite of the present application is tightly stacked into a spherical warm saturated structure and has high strength. This strength characteristic enables the perlite to withstand a certain pressure in filling applications and increase the stability of the structure. The perlite has a loose structure and can buffer the impact and vibration of the outside world on the inside of the filling material and protect the internal structure from damage. The perlite has a fine, uniform and dense texture and can withstand high temperatures. It has a high degree of fire resistance. The perlite effectively reduces the noise generated during the use of fitness equipment by reducing the expansion of pressure waves and suppressing acoustic vibrations.
[0017] The molecular sieves in the raw materials for preparing the reactive polyurethane hot melt adhesive of the present application can absorb moisture in the raw materials, reduce the water absorption rate during storage, avoid the reaction of water vapor with isocyanate, and improve the stability of the isocyanate component, thereby improving the shelf life of the reactive polyurethane hot melt adhesive; calcium sulfate whiskers can improve the water resistance and heat resistance of the product, and after heating, can better ensure the bonding performance and reduce costs; N-n-butyl-3-aminopropyltrimethoxysilane can improve the wettability of the colloid and the bonded object and enhance the bonding strength. Excessive content will reduce the hardness after curing.
[0018] This application introduces phosphorus and nitrogen elements by modifying polyether polyols. Nitrogen and phosphorus synergistically improve the flame retardant properties of polyurethane composites. At the same time, multiple benzene rings are introduced to further enhance its flame retardancy and corrosion resistance and improve the toughness of the material. When dibutyltin dilaurate is used as a catalyst, the activity of the two -NCO groups in the IPDI molecule is very different. The -NCO directly connected to the cyclohexane is less affected by the substituent and steric hindrance, and its activity is more than 10 times higher than that of the other -NCO group. Therefore, polyethylene glycol monomethyl ether is added dropwise to IPDI, and IPDI is always in excess, so that the highly active -NCO reacts first, and an intermediate product containing monoisocyanate can be obtained.
[0019] The molar ratio of bisphenol A epoxy resin to phenylphosphonic acid is greater than 2:1, and phenylphosphonic acid containing terminal epoxy groups is obtained. The terminal epoxy groups react with -NCO of the intermediate product to introduce hydrophilic polyethylene glycol segments into the molecule. Since phenylphosphonic acid has two active hydrogens, it can react with two bisphenol A epoxy resins and be capped by two epoxy groups. Therefore, two polyethylene glycol segments can be introduced into one polyether polyol molecule, which has better hydrophilicity and can effectively reduce the length of the hydrophilic segment in the molecule. At the same time, this branched structure can reduce the hydrodynamic volume of the molecule, improve fluidity, and improve the elasticity of the prepared polyurethane material.
[0020] According to some embodiments of the present application, the molar number of dibutyltin dilaurate in step S1 is 0.8-1.2% of the molar number of polyethylene glycol monomethyl ether.
[0021] According to some embodiments of the present application, the protective gas in step S2 is selected from one of nitrogen, helium, neon, and argon, for example, the protective gas is nitrogen. Nitrogen is widely available and has low production costs. It can form an oxygen-free environment to prevent epoxy groups, isocyanates, etc. from being oxidized and destroyed, and reduce the occurrence of side reactions. Rare gases such as helium, neon, and argon are stable in nature and are not easily involved in chemical reactions, which can reduce the generation of side reactions.
[0022] According to some embodiments of the present application, the molar ratio of the intermediate product to the phenylphosphonic acid in step S2 is (1.9-2.1):1; the molar ratio of the intermediate product to the phenylphosphonic acid containing a terminal epoxy group is controlled to be around 2:1 to facilitate the full reaction and improve the utilization rate of the raw materials.
[0023] According to some embodiments of the present application, the molar number of benzyltriethylammonium chloride in step S2 is 2-4% of the molar number of phenylphosphonic acid.
[0024] According to some embodiments of the present application, the resin particles are blended by polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of (1-2): 1. Polycarbonate is heat-resistant and impact-resistant, and has good mechanical properties. Acrylonitrile-butadiene-styrene resin has excellent comprehensive properties, excellent impact strength, wear resistance, chemical resistance, good molding and machining, and the blending of the two can improve the strength and impact resistance of the filling material.
[0025] According to some embodiments of the present application, the preparation method of the reactive polyurethane hot melt adhesive comprises the following steps: mixing polyester polyol, epoxy-modified polyether polyol, fumed silica, calcium sulfate whisker, and molecular sieve according to parts by weight, heating and stirring, adding acrylic resin powder when heated to 135-140°C, and stirring for 30-40 minutes until the acrylic resin is completely melted; slowly evacuating the vacuum and dehydrating for 1-2 hours under the condition of a vacuum degree of less than -0.096MPa; after the dehydration is completed, cooling to 115°C, adding diphenylmethane diisocyanate and N-n-butyl-3-aminopropyltrimethoxysilane, stirring for 10-15 minutes, and heating to 120°C for prepolymerization for 1.0-1.5 hours; cooling to 115°C, adding a catalyst and dodecyldimethyl tertiary amine, stirring for 5 minutes, heating to 118-120°C, and stirring for 1.0-1.5 hours under the condition of a vacuum degree of less than -0.096MPa to obtain a reactive polyurethane hot melt adhesive.
[0026] According to some embodiments of the present invention, the specific surface area of the fumed silica is 150-250 m 2 / g.
[0027] According to some embodiments of the present invention, the particle size of the calcium sulfate whiskers is 1200-1300 mesh.
[0028] According to some embodiments of the present application, the catalyst is compounded by dimorpholine diethyl ether and dibutyltin dilaurate in a weight ratio of (1-2):1.
[0029] According to some embodiments of the present application, the wood particles are selected from at least one of ash, beech, camphor, walnut, oak, birch, fir, elm, and redwood.
[0030] According to some embodiments of the present application, the average particle size of the wood particles is 3-6 mm. Wood particles within this particle size range are easy to combine with reactive polyurethane hot melt adhesive, taking into account the elasticity of the wood particles and the strength of the filling material, and enhancing the impact resistance of the filling material.
[0031] According to some embodiments of the present application, the average particle size of the perlite is 5-15 mm.
[0032] If the particle size of aggregates such as perlite is too large, the gaps between the large particles will be difficult to be filled by the reactive polyurethane hot melt adhesive, affecting the strength of the filling material. Conversely, if the particle size of aggregates such as perlite is too small, the reactive polyurethane hot melt adhesive will be difficult to fully bond, resulting in reduced bonding performance between the mixed raw materials, which will also affect the strength of the filling material.
[0033] According to some embodiments of the present application, the preparation method of the filling material is:
[0034] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0035] A2. Heat the mixed raw materials at 80-120°C for 30 min to obtain a filling material.
[0036] In a second aspect, an embodiment of the present application provides a fitness equipment core comprising the filling material.
[0037] According to an embodiment of the present application, a fitness equipment inner core including the filling material has at least the following beneficial effects:
[0038] The inner core of the fitness equipment of the present application has good mechanical properties and is not easy to deform. It also has good drop resistance and is not easy to break when impacted by external forces, and has a long service life.
[0039] According to some embodiments of the present application, the inner core of the fitness equipment further includes a metal frame.
[0040] Furthermore, the material of the metal frame is iron. Iron has high strength and high specific gravity, which can not only improve the mechanical properties of the inner core of the fitness equipment, but also has good heat transfer effect. The iron frame can fix the filling material, and the iron frame and the filling material can be better integrated when heated, and it is not easy to have gaps in subsequent use, thereby improving the bonding strength.
[0041] Furthermore, the metal frame is made by stamping and welding metal sheets.
[0042] Furthermore, the thickness of the metal sheet is 0.5 mm-1 mm.
[0043] In a third aspect, an embodiment of the present application provides a fitness equipment comprising the fitness equipment inner core.
[0044] A fitness equipment including the filling material according to an embodiment of the present application has at least the following beneficial effects:
[0045] The fitness equipment of the present application has good mechanical properties and is not easy to deform. It also has good drop resistance and is not easy to break when impacted by external forces, and has a long service life.
[0046] According to some embodiments of the present application, the fitness equipment includes a barbell, a dumbbell, and a kettlebell.
[0047] According to some embodiments of the present application, the fitness equipment further comprises an encapsulating layer.
[0048] Furthermore, the material of the rubber layer is selected from one of synthetic rubber, rubber particles and rubber plastic. Rubber, rubber particles and rubber plastic can further enhance the elasticity of the sheet-like accessories, so that the sheet-like accessories are not easy to damage the floor when they fall.
[0049] In a fourth aspect, the present application provides a method for preparing the fitness equipment, which is implemented by the following technical solutions:
[0050] A method for preparing fitness equipment comprises the following steps:
[0051] (1) mixing a reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water according to parts by weight, and stirring for 10 minutes to obtain a mixed raw material;
[0052] (2) filling the mixed raw material into a metal frame and sealing it;
[0053] (3) sandblasting the metal frame, cleaning it, and heating it at 80-120° C. for 30 min to obtain the inner core of the fitness equipment;
[0054] (4) A thermal bonding agent is applied to the surface of the inner core of the fitness equipment, and the rubber and the inner core of the fitness equipment are fused together by heating and vulcanization using a mold to obtain the fitness equipment.
[0055] The method for preparing the fitness equipment according to the embodiment of the present application has at least the following beneficial effects:
[0056] The present application adopts a method of first fusing the filler and then encapsulating with rubber to prepare the fitness equipment, which can ensure the mechanical strength of the inner core of the fitness equipment while taking into account the drop resistance. The fitness equipment has good integrity, and the inner core and the rubber coating layer of the fitness equipment are not easy to fall off during use. The fitness equipment is not easy to deform or break. The preparation method of the present application has simple steps, does not require the use of complex production equipment, has low cost, and is suitable for industrial production.
[0057] The present application further improves the mechanical strength of the fitness equipment by fusing the filling material into the interior of the metal frame, making it less likely to break or deform when subjected to external force impact. DETAILED DESCRIPTION
[0058] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0059] Preparation Example 1 of Epoxy-modified Polyether Polyol
[0060] Preparation of epoxy modified polyether polyols:
[0061] S1. Take 6 mol of isophorone diisocyanate, add 0.05 mol of dibutyltin dilaurate, heat to 35 ° C, gradually add 5 mol of polyethylene glycol monomethyl ether dropwise within 30 min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, distill at a temperature of 100 ° C and a vacuum of 8 kPa to obtain an intermediate product;
[0062] S2. Take 4.5 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid dropwise within 20 minutes. After the addition is completed, react for 2 hours. Add 0.06 mol of benzyl triethylamine chloride catalyst and 3.9 mol of the intermediate product, react until NCO% is less than 0.1%, and distill at a temperature of 95°C and a vacuum degree of 8 kPa to obtain epoxy-modified polyether polyol.
[0063] Preparation Example 2 of Epoxy-modified Polyether Polyol
[0064] Preparation of epoxy modified polyether polyols:
[0065] S1. Take 5.5 mol of isophorone diisocyanate, add 0.04 mol of dibutyltin dilaurate, heat to 35 ° C, gradually add 5 mol of polyethylene glycol monomethyl ether dropwise within 30 min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, distill at a temperature of 90 ° C and a vacuum of 8 kPa to obtain an intermediate product;
[0066] S2. Take 5 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid dropwise within 20 minutes. After the addition is completed, react for 3 hours. Add 0.04 mol of benzyl triethylamine chloride catalyst and 4 mol of the intermediate product, react until NCO% is less than 0.1%, and distill at a temperature of 105°C and a vacuum degree of 8 kPa to obtain epoxy-modified polyether polyol.
[0067] Preparation Example 3 of Epoxy-modified Polyether Polyol
[0068] Preparation of epoxy modified polyether polyols:
[0069] S1. Take 6.5 mol of isophorone diisocyanate, add 0.06 mol of dibutyltin dilaurate, heat to 35 ° C, gradually add 5 mol of polyethylene glycol monomethyl ether dropwise within 30 min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, distill at a temperature of 105 ° C and a vacuum of 8 kPa to obtain an intermediate product;
[0070] S2. Take 4 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid dropwise within 20 minutes. After the addition is completed, react for 2 hours. Add 0.08 mol of benzyl triethylamine chloride catalyst and 4.1 mol of the intermediate product, react until NCO% is less than 0.1%, and distill at a temperature of 90°C and a vacuum of 8 kPa to obtain epoxy-modified polyether polyol.
[0071] Epoxy modified polyether polyol comparative example 1
[0072] Preparation of epoxy modified polyether polyols:
[0073] Take 4.5 mol of bisphenol A epoxy resin and heat it to 90°C. Under a nitrogen protective gas atmosphere, gradually add 2 mol of phenylphosphonic acid within 20 minutes. After the addition is completed, react for 2 hours. Add 0.06 mol of benzyl triethylamine chloride catalyst and distill at a temperature of 95°C and a vacuum of 8 kPa to obtain epoxy-modified polyether polyol.
[0074] Preparation Example 1 of Reactive Polyurethane Hot Melt Adhesive
[0075] Preparation of reactive polyurethane hot melt adhesive: Raw materials were selected by weight: 15 parts of polyester polyol, 30 parts of epoxy-modified polyether polyol prepared in Preparation Example 1 of epoxy-modified polyether polyol, 5 parts of fumed silica, 7 parts of calcium sulfate whiskers, 8 parts of acrylic resin powder, 45 parts of diphenylmethane diisocyanate, 7 parts of N-n-butyl-3-aminopropyltrimethoxysilane, 2 parts of molecular sieves, 0.8 parts of catalyst, and 1 part of dodecyldimethyl tertiary amine; among them, polyester polyol was selected from HJ-3500 produced by Shandong Hengjiu Dafu New Materials Co., Ltd.; the specific surface area of fumed silica was 150-250m 2 / g; the particle size of the calcium sulfate whisker is 1200-1300 mesh; the catalyst is compounded by dimorpholine diethyl ether and dibutyltin dilaurate in a weight ratio of 2:1;
[0076] Polyester polyol, epoxy-modified polyether polyol, fumed silica, calcium sulfate whisker and molecular sieve are placed in a three-necked flask according to parts by weight, heated and stirred, and when heated to 138°C, acrylic resin powder is added, and stirred for 30 minutes until the acrylic resin is completely melted; vacuum is slowly evacuated, and dehydration is performed for 1.5 hours under the condition of vacuum degree less than -0.096MPa; after dehydration, the temperature is cooled to 115°C, diphenylmethane diisocyanate and N-n-butyl-3-aminopropyltrimethoxysilane are added, and after stirring for 12 minutes, the temperature is heated to 120°C for prepolymerization for 1.3 hours; the temperature is cooled to 115°C, a catalyst and dodecyldimethyl tertiary amine are added, and after stirring for 5 minutes, the temperature is heated to 120°C, and stirred for 1.2 hours under the condition of vacuum degree less than -0.096MPa to obtain a reactive polyurethane hot melt adhesive.
[0077] Preparation Example 2 of Reactive Polyurethane Hot Melt Adhesive
[0078] Preparation of reactive polyurethane hot melt adhesive: Raw materials were selected by weight: 10 parts of polyester polyol, 40 parts of epoxy-modified polyether polyol prepared in Preparation Example 1 of epoxy-modified polyether polyol, 2 parts of fumed silica, 10 parts of calcium sulfate whiskers, 6 parts of acrylic resin powder, 50 parts of diphenylmethane diisocyanate, 5 parts of N-n-butyl-3-aminopropyltrimethoxysilane, 5 parts of molecular sieves, 0.5 parts of catalyst, and 2 parts of dodecyldimethyl tertiary amine; among them, polyester polyol was selected from HJ-3500 produced by Shandong Hengjiu Dafu New Materials Co., Ltd.; the specific surface area of fumed silica was 150-250m 2 / g; the particle size of the calcium sulfate whisker is 1200-1300 mesh; the catalyst is compounded by dimorpholine diethyl ether and dibutyltin dilaurate in a weight ratio of 1:1;
[0079] Polyester polyol, epoxy-modified polyether polyol, fumed silica, calcium sulfate whisker and molecular sieve are placed in a three-necked flask according to parts by weight, heated and stirred, and when heated to 140°C, acrylic resin powder is added, and stirred for 40 minutes until the acrylic resin is completely melted; vacuum is slowly evacuated, and dehydration is performed for 1 hour under the condition of vacuum degree less than -0.096MPa; after dehydration, the temperature is cooled to 115°C, diphenylmethane diisocyanate and N-n-butyl-3-aminopropyltrimethoxysilane are added, and after stirring for 15 minutes, the temperature is heated to 120°C for prepolymerization for 1.0 hour; the temperature is cooled to 115°C, a catalyst and dodecyldimethyl tertiary amine are added, and after stirring for 5 minutes, the temperature is heated to 118°C, and stirred for 1.5 hours under the condition of vacuum degree less than -0.096MPa to obtain a reactive polyurethane hot melt adhesive.
[0080] Reactive polyurethane hot melt adhesive comparative example 1
[0081] Preparation of reactive polyurethane hot melt adhesive: Raw materials are selected by weight: 15 parts of polyester polyol, 30 parts of epoxy-modified polyether polyol prepared in Example 1 of epoxy-modified polyether polyol, 5 parts of fumed silica, 7 parts of calcium sulfate whiskers, 8 parts of acrylic resin powder, 45 parts of diphenylmethane diisocyanate, 7 parts of N-n-butyl-3-aminopropyltrimethoxysilane, 2 parts of molecular sieves, 0.8 parts of catalyst, and 1 part of dodecyldimethyl tertiary amine; among them, the polyester polyol is HJ-3500 produced by Shandong Hengjiu Dafu New Materials Co., Ltd.; the specific surface area of fumed silica is 150-250m 2 / g; the particle size of the calcium sulfate whisker is 1200-1300 mesh; the catalyst is compounded by dimorpholine diethyl ether and dibutyltin dilaurate in a weight ratio of 2:1;
[0082] Polyester polyol, epoxy-modified polyether polyol, fumed silica, calcium sulfate whisker and molecular sieve are placed in a three-necked flask according to parts by weight, heated and stirred, and when heated to 138°C, acrylic resin powder is added, and stirred for 30 minutes until the acrylic resin is completely melted; vacuum is slowly evacuated, and dehydration is performed for 1.5 hours under the condition of vacuum degree less than -0.096MPa; after dehydration, the temperature is cooled to 115°C, diphenylmethane diisocyanate and N-n-butyl-3-aminopropyltrimethoxysilane are added, and after stirring for 12 minutes, the temperature is heated to 120°C for prepolymerization for 1.3 hours; the temperature is cooled to 115°C, a catalyst and dodecyldimethyl tertiary amine are added, and after stirring for 5 minutes, the temperature is heated to 120°C, and stirred for 1.2 hours under the condition of vacuum degree less than -0.096MPa to obtain a reactive polyurethane hot melt adhesive.
[0083] Reactive polyurethane hot melt adhesive comparative example 2
[0084] Preparation of reactive polyurethane hot melt adhesive: Raw materials were selected by weight: 15 parts of polyester polyol, 30 parts of common polyether polyol, 5 parts of fumed silica, 7 parts of calcium sulfate whisker, 8 parts of acrylic resin powder, 45 parts of diphenylmethane diisocyanate, 7 parts of N-n-butyl-3-aminopropyltrimethoxysilane, 2 parts of molecular sieve, 0.8 parts of catalyst, and 1 part of dodecyldimethyl tertiary amine; among them, polyester polyol was HJ-3500 produced by Shandong Hengjiu Dafu New Materials Co., Ltd.; the specific surface area of fumed silica was 150-250m 2 / g; the particle size of the calcium sulfate whisker is 1200-1300 mesh; the catalyst is compounded by dimorpholine diethyl ether and dibutyltin dilaurate in a weight ratio of 2:1;
[0085] Polyester polyol, common polyether polyol, fumed silica, calcium sulfate whisker and molecular sieve are put into a three-necked flask according to weight parts, heated and stirred, and acrylic resin powder is added when heated to 138°C, and stirred for 30 minutes until the acrylic resin is completely melted; vacuum is slowly drawn, and dehydration is carried out for 1.5 hours under the condition of vacuum degree less than -0.096MPa; after dehydration, the temperature is cooled to 115°C, diphenylmethane diisocyanate and N-n-butyl-3-aminopropyltrimethoxysilane are added, and after stirring for 12 minutes, the temperature is heated to 120°C for prepolymerization for 1.3 hours; the temperature is cooled to 115°C, a catalyst and dodecyldimethyl tertiary amine are added, and after stirring for 5 minutes, the temperature is heated to 120°C, and the vacuum degree is less than -0.096MPa. Stir for 1.2 hours to obtain a reactive polyurethane hot melt adhesive.
[0086] Example 1
[0087] Preparation of filling materials for fitness equipment: Select raw materials by weight: 8 parts of reactive polyurethane hot melt adhesive prepared in Preparation Example 1 of reactive polyurethane hot melt adhesive, 12 parts of wood particles, 18 parts of perlite, 8 parts of rubber particles, 7 parts of resin particles, 10 parts of fly ash, and 2 parts of water; wherein the wood particles are formed by mixing camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5 mm; the average particle size of the perlite is 10 mm; the resin particles are formed by mixing polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of 2:1;
[0088] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0089] A2. Heat the mixed raw materials at 100°C for 30 minutes to obtain a filling material.
[0090] Example 2
[0091] Preparation of filling materials for fitness equipment: Select raw materials by weight: 5 parts of reactive polyurethane hot melt adhesive prepared in Preparation Example 1 of reactive polyurethane hot melt adhesive, 15 parts of wood particles, 10 parts of perlite, 12 parts of rubber particles, 5 parts of resin particles, 15 parts of fly ash, and 1 part of water; wherein the wood particles are selected from elm; the average particle size of the wood particles is 6 mm; the average particle size of the perlite is 15 mm; the resin particles are formed by blending polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of 1:1;
[0092] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0093] A2. Heat the mixed raw materials at 120°C for 30 minutes to obtain a filling material.
[0094] Example 3
[0095] Preparation of filling materials for fitness equipment: Select raw materials by weight: 10 parts of reactive polyurethane hot melt adhesive prepared in Preparation Example 1, 8 parts of wood particles, 25 parts of perlite, 5 parts of rubber particles, 12 parts of resin particles, 5 parts of fly ash, and 3 parts of water; wherein the wood particles are selected from walnut wood; the average particle size of the wood particles is 3 mm; the average particle size of the perlite is 5 mm; the resin particles are formed by blending polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of 2:1;
[0096] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0097] A2. Heat the mixed raw materials at 80°C for 30 minutes to obtain a filling material.
[0098] Comparative Example 1
[0099] Preparation of filling materials for fitness equipment: Select raw materials by weight: 8 parts of reactive polyurethane hot melt adhesive prepared in comparative example 1, 12 parts of wood particles, 18 parts of perlite, 8 parts of rubber particles, 7 parts of resin particles, 10 parts of fly ash, and 2 parts of water; wherein the wood particles are formed by mixing camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5 mm; the average particle size of the perlite is 10 mm; the resin particles are formed by mixing polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of 2:1;
[0100] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0101] A2. Heat the mixed raw materials at 100°C for 30 minutes to obtain a filling material.
[0102] Comparative Example 2
[0103] Preparation of filling materials for fitness equipment: Select raw materials by weight: 8 parts of reactive polyurethane hot melt adhesive prepared in comparative example 2 of reactive polyurethane hot melt adhesive, 12 parts of wood particles, 18 parts of perlite, 8 parts of rubber particles, 7 parts of resin particles, 10 parts of fly ash, and 2 parts of water; wherein the wood particles are formed by mixing camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5 mm; the average particle size of the perlite is 10 mm; the resin particles are formed by mixing polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of 2:1;
[0104] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0105] A2. Heat the mixed raw materials at 100°C for 30 minutes to obtain a filling material.
[0106] Comparative Example 3
[0107] Preparation of filling materials for fitness equipment: Select raw materials by weight: 8 parts of reactive polyurethane hot melt adhesive prepared in Preparation Example 1 of reactive polyurethane hot melt adhesive, 12 parts of wood particles, 8 parts of rubber particles, 7 parts of resin particles, 10 parts of coal ash, and 2 parts of water; wherein the wood particles are formed by mixing camphor wood and oak in a weight ratio of 1:1; the average particle size of the wood particles is 5 mm; the resin particles are formed by mixing polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of 2:1;
[0108] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0109] A2. Heat the mixed raw materials at 100°C for 30 minutes to obtain a filling material.
[0110] Comparative Example 4
[0111] Preparation of filling materials for fitness equipment: Select raw materials by weight: 8 parts of reactive polyurethane hot melt adhesive prepared in Preparation Example 1, 12 parts of wood particles, 18 parts of perlite, 8 parts of rubber particles, 10 parts of fly ash, and 2 parts of water; wherein the wood particles are made of camphor wood and oak mixed in a weight ratio of 1:1; the average particle size of the wood particles is 5 mm; the average particle size of the perlite is 10 mm;
[0112] A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material;
[0113] A2. Heat the mixed raw materials at 100°C for 30 minutes to obtain a filling material.
[0114] Experimental example
[0115] The filling materials for fitness equipment prepared in Examples 1-3 and Comparative Examples 1-4 were tested for compressive strength, flexural strength, splitting tensile strength, and impact strength, respectively. The testing methods are as follows:
[0116] The compressive strength is tested according to GB / T 50081-2019;
[0117] The flexural strength is tested according to the standard of GB / T 50081-2019;
[0118] The splitting tensile strength is tested according to the standard of GB / T 50081-2019;
[0119] The test method of impact strength is as follows: the filling material sample is made into a cube with a side length of 10 cm. This experiment adopts the drop hammer method for testing, in which the hammer weighs 3 kg, the lower end of the hammer is a spherical surface, and the drop height is 0.53 m. The impact resistance of concrete is expressed by the energy consumed per unit volume when the first visible crack appears on the surface of the sample under the repeated impact of the drop hammer. It is called impact strength and is expressed by the following formula: R 冲 =9.8GHn / V; where R 冲 -Impact strength (J / cm 3 ), G-impact hammer mass (kg), H-hammer drop height (m), n-impact number (times), V-sample volume (cm 3 ).
[0120] The test data is shown in Table 1 below:
[0121] Table 1
[0122]
[0123] It can be seen from Table 1 that the filling materials prepared in Examples 1-3 of the present application have excellent compressive strength, flexural strength, splitting tensile strength, and impact strength.
[0124] The reactive polyurethane hot melt adhesive prepared in Comparative Example 1 is selected from the raw materials for preparing the reactive polyurethane hot melt adhesive. The epoxy-modified polyether polyol in the raw materials for preparing the reactive polyurethane hot melt adhesive does not introduce isophorone diisocyanate, and the rest is the same as Example 1. The flexural strength, splitting tensile strength, impact strength and other properties of the filling material prepared in Comparative Example 1 are significantly inferior to those in Example 1 of the present application, indicating that the specific combination of the components of the reactive polyurethane hot melt adhesive in the present application is very important for improving the performance of the filling material. The introduction of isophorone diisocyanate into the epoxy-modified polyether polyol can make the crosslinking more sufficient, improve the performance of the reactive polyurethane hot melt adhesive, and further improve the flexural and drop resistance of the filling material.
[0125] Reactive polyurethane hot melt adhesive is selected as the raw material for the preparation of the reactive polyurethane hot melt adhesive prepared in Comparative Example 2, and ordinary polyether polyol is selected as the raw material for the preparation of the reactive polyurethane hot melt adhesive, and the rest are the same as Example 1. The flexural strength, splitting tensile strength, impact strength and other properties of the filling material prepared in Comparative Example 2 are obviously inferior to those in Example 1 of the present application, indicating that the specific combination of the components of the reactive polyurethane hot melt adhesive in the present application is very important for improving the performance of the filling material. Epoxy resin modification can make the cross-linking of the polyether polyol more sufficient, improve the performance of the reactive polyurethane hot melt adhesive, and further improve the flexural resistance and fall resistance of the filling material.
[0126] The preparation raw materials of Comparative Example 3 do not contain perlite, and the rest are the same as Example 1. The flexural strength, splitting tensile strength, impact strength and other properties of the filling material prepared in Comparative Example 3 are obviously inferior to those of Example 1 of the present application, indicating that the perlite of the present application has higher strength, can withstand a certain pressure, increase the stability of the structure, buffer the impact and vibration of the outside world on the inside of the filling material, and protect the internal structure from damage, thereby improving the flexural resistance and drop resistance of the filling material.
[0127] The raw materials prepared in Comparative Example 4 do not contain resin particles, and the rest are the same as Example 1. The compressive strength, flexural strength, splitting tensile strength, and impact strength of the filling material prepared in Comparative Example 4 are all poor, indicating that the resin particles of the present application can penetrate into the tiny pores of the raw material matrix after hot melting, and form mechanical bite and chemical bonding with the raw materials, thereby enhancing the bonding force between the raw materials and enhancing the strength and stability of the filling material.
[0128] Fitness equipment preparation example 1
[0129] Preparation of dumbbells:
[0130] (1) Using the raw materials selected in Example 1, reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed according to weight parts, and stirred for 10 minutes to obtain a mixed raw material;
[0131] (2) filling the mixed raw material into an iron frame and sealing it; wherein the iron frame is made by stamping and welding an iron sheet with a thickness of 0.8 mm;
[0132] (3) The iron frame is sandblasted and cleaned, and heated at 100° C. for 30 min to obtain the dumbbell inner core;
[0133] (4) A thermal bonding agent is applied to the surface of the dumbbell inner core, and the rubber and the dumbbell inner core are fused together by heating and vulcanization using a mold to obtain a dumbbell.
[0134] The prepared dumbbells were tested and found to be able to withstand 20,000 drops. They are strong, durable, and have good vibration reduction effects, and will not cause damage to the ground.
[0135] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A filling material for fitness equipment, characterized in that: The preparation comprises the following raw materials in parts by weight: 5-10 parts of reactive polyurethane hot melt adhesive, 8-15 parts of wood particles, 10-25 parts of perlite, 5-12 parts of rubber particles, 5-12 parts of resin particles, 5-15 parts of fly ash, and 1-3 parts of water; The reactive polyurethane hot melt adhesive comprises the following raw materials in parts by weight: 10-20 parts of polyester polyol, 20-40 parts of epoxy-modified polyether polyol, 2-6 parts of fumed silica, 5-10 parts of calcium sulfate whiskers, 6-10 parts of acrylic resin powder, 30-50 parts of diphenylmethane diisocyanate, 5-10 parts of N-n-butyl-3-aminopropyltrimethoxysilane, 1-5 parts of molecular sieve, 0.5-1 parts of catalyst, and 0.5-2 parts of dodecyldimethyl tertiary amine; The preparation method of the epoxy-modified polyether polyol comprises the following steps: S1. Take isophorone diisocyanate, add dibutyltin dilaurate, heat to 30-40 ° C, gradually add polyethylene glycol monomethyl ether dropwise within 25-35min, determine the -NCO content by di-n-butylamine titration, react until NCO% is stable, and distill under reduced pressure at a temperature of 90-105 ° C to obtain an intermediate product; S2. Take bisphenol A epoxy resin and heat it to 85-95 ° C. Under a protective gas atmosphere, phenylphosphonic acid is gradually added dropwise within 18-25 min. After the addition is completed, react for 2-3 hours, add benzyl triethylamine chloride and the intermediate product, react until NCO% is less than 0.1%, and distill under reduced pressure at 90-105 ° C to obtain epoxy-modified polyether polyol; The molar ratio of the polyethylene glycol monomethyl ether to the isophorone diisocyanate in step S1 is 1:(1-1.3); The molar ratio of the bisphenol A epoxy resin to the phenylphosphonic acid in step S2 is (4-5):
2.
2. A filling material for fitness equipment according to claim 1, characterized in that: The preparation method of the reactive polyurethane hot melt adhesive comprises the following steps: mixing polyester polyol, epoxy-modified polyether polyol, fumed silica, calcium sulfate whisker and molecular sieve according to parts by weight, heating and stirring, adding acrylic resin powder when heated to 135-140° C., stirring for 30-40 minutes, until the acrylic resin is completely melted; slowly evacuating the mixture, and dehydrating the mixture for 1-2 hours under the condition that the vacuum degree is less than -0.096MPa; after the dehydration is completed, cooling the mixture to 115° C., adding diphenylmethane diisocyanate and N-n-butyl-3-aminopropyltrimethoxysilane, stirring for 10-15 minutes, heating the mixture to 120° C. for prepolymerization reaction for 1.0-1.5 hours; cooling the mixture to 115° C., adding a catalyst and dodecyl dimethyl tertiary amine, stirring for 5 minutes, heating the mixture to 118-120° C., and stirring the mixture for 1.0-1.5 hours under the condition that the vacuum degree is less than -0.096MPa, to obtain the reactive polyurethane hot melt adhesive.
3. The filling material for fitness equipment according to claim 1, characterized in that: The molar ratio of the intermediate product to the phenylphosphonic acid in step S2 is (1.9-2.1):1, and / or the molar number of benzyltriethylammonium chloride in step S2 is 2-4% of the molar number of phenylphosphonic acid.
4. The filling material for fitness equipment according to claim 1, characterized in that: The resin particles are prepared by blending polycarbonate and acrylonitrile-butadiene-styrene resin in a weight ratio of (1-2):
1.
5. The filling material for fitness equipment according to claim 1, characterized in that: The catalyst is prepared by compounding dimorpholine diethyl ether and dibutyltin dilaurate in a weight ratio of (1-2):
1.
6. The filling material for fitness equipment according to claim 1, characterized in that: The preparation method of the filling material comprises the following steps: A1. According to parts by weight, the reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water were mixed and stirred for 10 minutes to obtain a mixed raw material; A2. Heat the mixed raw materials at 80-120°C for 30 min to obtain a filling material.
7. A fitness equipment inner core comprising the filling material according to any one of claims 1 to 6, characterized in that: The inner core of the fitness equipment also contains a metal frame.
8. The fitness equipment inner core according to claim 7, characterized in that: The material of the metal frame is iron; the metal frame is made by stamping and welding metal sheets.
9. A fitness equipment comprising the fitness equipment core according to claim 7 or 8, characterized in that: The fitness equipment includes barbells, dumbbells and kettlebells.
10. A method for preparing the fitness equipment according to claim 9, characterized in that: The following steps are involved: (1) mixing a reactive polyurethane hot melt adhesive, wood particles, perlite, rubber particles, resin particles, fly ash and water according to parts by weight, and stirring for 10 minutes to obtain a mixed raw material; (2) filling the mixed raw material into a metal frame and sealing it; (3) sandblasting the metal frame, cleaning it, and heating it at 80-120° C. for 30 min to obtain the inner core of the fitness equipment; (4) A thermal bonding agent is applied to the surface of the inner core of the fitness equipment, and the rubber and the inner core of the fitness equipment are fused together by heating and vulcanization using a mold to obtain the fitness equipment.